Geographical distribution of Dyckia walteriana (Bromeliaceae), a recently described and endangered species endemic to the Serra Geral formation, southern Brazil - Musegante, João Vitor Da R.; Ribeiro, José Eduardo L. Da S.; Ferraz, José Roberto; Oliveira, Paolla Ody De; Bianchini, Edmilson; Medri, Cristiano (Phytotaxa, 2020)
Dyckia walteriana is a recently described rupicolous bromeliad, whose only officially known population is located on a basaltic outcrop in the Serra Geral formation, north of Paraná state, Brazil. Unfortunately, the population of the type locality was dramatically reduced in 2018 by an intentional fire. The main objectives of this work were to know the geographical distribution of D. walteriana, seeking the registration of new populations, and, through a rapid assessment, establish the risk of extinction of each one. We selected 40 sites with rocky outcrops located between the third and second plateaus of Paraná state, Brazil, within the Serra Geral formation. Twelve populations of D. walteriana were found occupying “islands” of basaltic rocks. The extent of occurrence of the species corresponds to a polygon of 533 km2, with an occupancy area of 0.71 km2. Of the 12 populations, only four presented no or low risk of extinction, while eight presented medium to extreme risk of extinction in the next 10 years. D. walteriana falls into the category “critically endangered”, demanding urgent measures for the conservation of relictual populations.